PENGAMBDIAN KEPADA MASYARAKAT MENGENAI DELAPAN FUNGSI KELUARGA SESUAI DENGAN PERATURAN PEMERINTAH NO.21 TAHUN 1994 TENTANG PENYELENGARAAN PEMBANGUNAN KELUARGA SEJAHTERA - Sri Utaminingsih; Endang Prastini; Djoko Somanto; Sucipto Sucipto; Ferry Kurniawan (LPPM Universitas Pamulang, 2020)
This community service activity aims to provide an understanding of how society views the sustainability of family life by paying attention to the eight family functions. It is hoped that this understanding can be applied in everyday life. Lack of public knowledge regarding the understanding of the eight functions of the family in carrying out their lives can trigger various problems, even conflicts between fellow family members. A prosperous and harmonious family is one of the goals of family ties. But in reality humans are not free from mistakes. Mistakes made in the family can trigger conflicts in the family and this can be fatal, especially if allowed to drag on and can even lead to the destruction of households and families.Keywords: Function, Family, Society